Synthesis of 5-hydroxymethylfurfural from glucose using H-Beta catalyst treated with phosphoric acid in one-pot biphasic solvent system. Issue 22 (17th November 2019) - Sansuk, Sira; Subsadsana, Maliwan
ABSTRACT: The production of 5-hydroxymethylfurfural (5-HMF) from glucose by using phosphoric acid (H3 PO4 ) treated H-Beta zeolite (P-H-Beta) as the catalyst in a one-pot biphasic solvent system is presented. The catalysts with varied contents of H3 PO4 over Beta-zeolite were synthesized by wet method and characterized by X-ray diffraction, scanning electron microscopy, fourier transform infrared spectroscopy, and NH3 -temperature-programmed desorption. Under the optimized catalytic conditions, the catalyst prepared by the treatment of H-Beta zeolite with 2 M H3 PO4 (2P-H-Beta) gave high conversion with almost 54% yield of 5-HMF at 150°C for 90 min reaction time and 0.1:1 mass ratio of catalyst to glucose with the THF/NaCl/H2 O solvent system. This resulted from the appropriate acidity of the strong acid sites on the catalyst which promoted the formation of 5-HMF and its effective partition in the biphasic H2 O/THF/NaCl solvent system.